2010
DOI: 10.1111/j.1365-2516.2010.02383.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of low frequency bleeding data: the association of joint bleeds according to baseline FVIII activity levels

Abstract: Many studies in the field of haemophilia and other coagulation deficiencies require analyses of bleeding frequencies. In haemophilia, the association of bleeding frequency with factor VIII (FVIII) activity levels is known from experience, but significant results are lacking. Bleeding frequencies in haemophilia are highly skewed count data, with large proportions of zeros. Both the skewness and the high amount of zeros pose a problem for standard (linear) modelling techniques. This study investigated the optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
175
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(180 citation statements)
references
References 9 publications
4
175
0
1
Order By: Relevance
“…In addition, recent data suggest that hemophilia B is associated with a less severe bleeding phenotype than hemophilia A, although the data are inconsistent between studies. [2][3][4][5][6] In a study by den Uijl et al, 7 rates of joint bleeding were found to decrease by 18% for each 1% increase in baseline FA level among 433 Dutch patients with moderate or mild hemophilia A who were receiving on-demand therapy. Limitations of the study were the small number of patients studied, the single data capture point for each patient, and the lack of data from patients with hemophilia B.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, recent data suggest that hemophilia B is associated with a less severe bleeding phenotype than hemophilia A, although the data are inconsistent between studies. [2][3][4][5][6] In a study by den Uijl et al, 7 rates of joint bleeding were found to decrease by 18% for each 1% increase in baseline FA level among 433 Dutch patients with moderate or mild hemophilia A who were receiving on-demand therapy. Limitations of the study were the small number of patients studied, the single data capture point for each patient, and the lack of data from patients with hemophilia B.…”
Section: Introductionmentioning
confidence: 97%
“…Limits of the middle 50% of the data (IQR limits)* with mild haemophilia showing that those with endogenous FVIII levels below 3% were at high risk of bleeding and consequently of arthropathy, while those with levels above 10% had a significantly lower risk [4]. Moreover, Ahlberg looking at the Swedish cohort of patients on prophylaxis suggested that a FVIII trough level of about 3% would be enough to lower the incidence of arthropathy in most cases [7].…”
Section: Product and Dosing Medianmentioning
confidence: 99%
“…It has been shown that joint bleeds are absent in patients with endogenous factor VIII (FVIII) levels approaching 12%. Patients with low baseline FVIII levels (<3%) seem to have the highest risk for joint bleeds and those with clotting factor activity levels of 10% and higher seem to have a very low risk [4]. Already in 1965 Ahlberg showed that in patients on prophylaxis with plasma trough levels above 3% arthropathy was rare and milder [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations